2016
DOI: 10.1136/bmjopen-2016-013122
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nurses’ changing perceptions when trained to implement a self-management programme for dual sensory impaired older adults in long-term care: a qualitative study

Abstract: ObjectivesTo gain insights into the process of nurses’ changing perceptions when trained to implement a self-management programme for dual sensory impaired older adults in long-term care, and into the factors that contributed to these changes in their perceptions.DesignQualitative study alongside a cluster randomised controlled trial.Setting17 long-term care homes spread across the Netherlands.Participants34 licensed practical nurses supporting 54 dual sensory impaired older adults.InterventionA 5-month traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In the case of older adults with DSI, one study has explored nurses' roles and perceptions of a selfmanagement rehabilitation strategy for older adults in long-term care with DSI (Roets-Merken et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of older adults with DSI, one study has explored nurses' roles and perceptions of a selfmanagement rehabilitation strategy for older adults in long-term care with DSI (Roets-Merken et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In their longitudinal qualitative study, Roets-Merken et al (2016) found that nurses initially held negative perceptions about the benefits of a self-management program for individuals with DSI. Yet, after working with these individuals, the nurses had a more positive perspective on the benefits of the program, and they also gained insights concerning adaptations needed in their approach to better support this clientele.…”
Section: Introductionmentioning
confidence: 99%
“…At the start of the intervention period, we observed a similar lack of partnership between the DSI older adults and their nurse. 44 The feelings of partnership only developed after nurses and older adults started a dialogue based on the SMP-DSI steps.…”
Section: Discussionmentioning
confidence: 99%
“…However, nurses’ changing perceptions in the course of the intervention, starting from fairly negative to positive perceptions (as reported in our parallel study), might have negatively affected the results. 44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation